The influence of swimming learning method using swimming board towards students’ interest in freestyle - Tjung Hauw Sin; Fakhrina Hudayani (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2020)
The problem in this study is the lack of student interest in freestyle swimming. The purpose of this study was to investigate the effect of swimming learning methods using swimming boards and interest in freestyle swimming skills. This type of research is quantitative using quasi-experimental research with a population of elementary school students in the city of Padang, sampling techniques using random purposive sampling, amounting to 26 people, determining the distribution of groups by matching techniques. The study design was carried out pre-test, then treated for 14 meetings and carried out post-test. The test instrument used was the ability to swim freestyle. By using the normality test (liliefors) and data analysis techniques with the t-test, at a significant level (α = 0.05). Then the results of the study showed that: (1) There was a significant influence between the learning methods using the swimming board on students' interest in freestyle swimming, with the results of t-count (15.37) t-table (1.81).